2020
DOI: 10.1002/lary.29256
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Dementia Benefit From Cochlear Implantation?

Abstract: BACKGROUNDDementia negatively impacts quality of life and is likely to become more prevalent in the rapidly aging population of the United States. It is estimated that the number of people living with dementia will triple by 2050 and care of these patients will cost approximately $1.5 trillion annually. In addition, dementia places an enormous emotional toll on a patient's family and loved ones. Targeting modifiable risk factors may delay further cognitive decline and help manage dementia, providing therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Similarly, a study included 70 hearing-impaired elderly patients (45% with MCI before surgery) and showed that cognitive function of 10% of the participants with MCI became normal in cognitive function 7 years after cochlear implantation (Mosnier et al, 2018). These findings may highlight the possibility that effective treatment for hearing loss could improve cognitive performance and reduce the incidence of dementia (Darwich et al, 2020). Future clinical studies are warranted to validate these hypotheses.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, a study included 70 hearing-impaired elderly patients (45% with MCI before surgery) and showed that cognitive function of 10% of the participants with MCI became normal in cognitive function 7 years after cochlear implantation (Mosnier et al, 2018). These findings may highlight the possibility that effective treatment for hearing loss could improve cognitive performance and reduce the incidence of dementia (Darwich et al, 2020). Future clinical studies are warranted to validate these hypotheses.…”
Section: Discussionmentioning
confidence: 96%
“…This is especially relevant considering that CI treatment could counteract or at least delay dementia. Further research is needed to understand the interrelationship between cognitive decline or dementia and hearing loss [ 52 ]. This suggests that if the influence of CI treatment on cognitive decline was factored in, the cost-effectiveness and effectiveness of CI provision would be even greater.…”
Section: Discussionmentioning
confidence: 99%
“…The general pattern was for improvement, although because there were only two studies that included a control group, it is difficult to be sure whether these apparent improvements in cognitive test performance are due to the cochlear implant, due to a retest effect, or simply due to better audibility of cognitive tests with a spoken component. Note that the potential for hearing interventions for improving cognition and preventing dementia is a different issue to improving outcomes for people living with dementia [37].…”
Section: Cognitive Outcomesmentioning
confidence: 99%